Regional economic trends and South Asian security - Iftekharuzzaman; Regional Centre for Strategic Studies (Colombo, Sri Lanka) (New Delhi : Manohar ; Dhaka : University Press, 1997)
Contributed articles.
"Regional Centre for Strategic Studies, Colombo."
Includes bibliographical references.
Keywords: National security -- South Asia; South Asia -- Foreign relations; South Asia -- Economic conditions; South Asia -- Economic policy